Implantation of a neoantigen-targeted hydrogel vaccine prevents recurrence of pancreatic adenocarcinoma after incomplete resection. (1st January 2021) - Delitto, Daniel; Zabransky, Daniel J.; Chen, Fangluo; Thompson, Elizabeth D.; Zimmerman, Jacquelyn W.; Armstrong, Todd D.; Leatherman, James M.; Suri, Reecha; Lopez-Vidal, Tamara Y.; Huff, Amanda L.; Lyman, Melissa R.; Guinn, Samantha R.; et al.
ABSTRACT: Tumor involvement of major vascular structures limits surgical options in pancreatic adenocarcinoma (PDAC), which in turn limits opportunities for cure. Despite advances in locoregional approaches, there is currently no role for incomplete resection. This study evaluated a gelatinized neoantigen-targeted vaccine applied to a grossly positive resection margin in preventing local recurrence. Incomplete surgical resection was performed in mice bearing syngeneic flank Panc02 tumors, leaving a 1 mm rim adherent to the muscle bed. A previously validated vaccine consisting of neoantigen peptides, a stimulator of interferon genes (STING) agonist and AddaVax TM (termed PancVax) was embedded in a hyaluronic acid hydrogel and applied to the tumor bed. Tumor remnants, regional lymph nodes, and spleens were analyzed using histology, flow cytometry, gene expression profiling, and ELISPOT assays. The immune microenvironment at the tumor margin after surgery alone was characterized by a transient influx of myeloid-derived suppressor cells (MDSCs), prolonged neutrophil influx, and near complete loss of cytotoxic T cells. Application of PancVax gel was associated with enhanced T cell activation in the draining lymph node and expansion of neoantigen-specific T cells in the spleen. Mice implanted with PancVax gel demonstrated no evidence of residual tumor at two weeks postoperatively and healed incisions at two months postoperatively without local recurrence. In summary, application of PancVax gel at a grossly positive tumor margin led to systemic expansion of neoantigen-specific T cells and effectively prevented local recurrence. These findings support further work into locoregional adjuncts to immune modulation in PDAC.